178k views
4 votes
we have first we replace the functions;sin x/1-cos x= cos x+cot xsin x/1-cosx=1/secx +cosx/sen xsin x/ 1-cos x =1/(1/cos x) + cos x/sen xsin x /sin x= 1/cos x + cos x/sen xsin x/sin x= (1/cos x=sin x) + cos x/sin x;sin x/sin x= sin(2) mean squared; +cos x;then the function remains sine squared x + cosine squared of xsin(2)x +cos (2) x = 1

User Nourza
by
5.5k points

1 Answer

3 votes

we have first we replace the functions;



sin x/1-cos x= cos x+cot x

sin x/1-cosx=1/secx +cosx/sen x

sin x/ 1-cos x =1/(1/cos x) + cos x/sen x

sin x /sin x= 1/cos x + cos x/sen x

sin x/sin x= (1/cos x=sin x) + cos x/sin x;



sin x/sin x= sin(2) mean squared; +cos x;





then the function remains sine squared x + cosine squared of x

sin(2)x +cos (2) x = 1

User Alexej Sommer
by
5.7k points